Additional Complex Behaviors, Bifurcations and Chaos, in the Passive Walk of the Compass-Type Bipedal Robot. Issue 17 (2021) - Added, Essia; Gritli, Hassène; Belghith, Safya
Abstract: The compass-type bipedal robot is an impulsive hybrid mechanical system that can produce complex behaviors, chaos and bifurcations. In this work, we analyze the passive dynamic walking of the compass robot to further explore its complexity and these nonlinear phenomena while descending inclined surfaces. The bifurcation diagrams are mainly adopted to investigate the complex walking behaviors by varying the slope angle and the length of the lower-leg segment. We show exhibition of the period-doubling bifurcation, the Neimark-Sacker bifurcation, the period-remerging phenomenon, bubbles and chaos. The Poincaré map and the state space are also used to further analyze these complex behaviors.